PENGARUH PENGELUARAN PEMERINTAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO PADA KORIDOR UTARA SELATAN DI PROVINSI JAWA TIMUR - Latifa Insaf Maulida; Idah Zuhroh (Jurnal Ilmu Ekonomi JIE, 2017)
Influence of Goverment Expenditure to Gross Regional Domestic Procuct. It is common in developing countries like Indonesia, the government plays an important role on the economics. The government expenditure practically effect the economicsoactivity, not only because the expenditure can create the development process but also as the one of the component of aggregate demand that could increase the domestic products. This study aims to determine the impact of government expenditure towards gross regional domestic procuct at north south corridor of east java province in period 2008 – 2016. This study are focused to two majors of government expenditure; operational expenditure and capital expenditure. The analysis of data were conducted using multiple regression of panel data for the hypotheses tested. The result shows that the hypotheses proposed in this sudy is supported.Keyword: goverment expenditure, Gross Regional Domestic Procuct, north south coridor.